Expenditure on Fixed Assets for Environmental Protection in Poland After Accession to The European Union - Joanna SZYMAŃSKA; Anna S. KOWALSKA; Anna OLSZAŃSKA; Klaudia GURKOWA (Communications of International Proceedings, 2022)
The article presents changes in expenditures incurred for the development of fixed assets related to the protection of the natural environment in Poland in total, in selected years from 2005 to 2020. The structure of the expenditure according to the investment directions and their sources was analysed. Selected effects of incurred expenditures in terms of the length of the distribution sewage network with collectors, the number of municipal sewage treatment plants and the reduction of the total emission of selected atmospheric air pollutants were presented. The study used desk research methods, including descriptive, analytical, mathematical and statistical ones. For the purposes of this study, trends in the analysed numerical data were determined and the correlation coefficients between the selected numerical data were calculated.
Keywords: environmental protection; Poland; expenditure on fixed assets